1978
DOI: 10.1143/ptp.59.1401
|View full text |Cite
|
Sign up to set email alerts
|

Self-Diffusion and Glass Transition of the Soft-Core Model

Abstract: The soft-core model with the inverse power potential ¢(r) =E(CJ/r)n, has been studied as a simple, but realistic model for actual simple liquids like argonY -3 ) With the molecular dynamics calculations the self-diffusion coefficient of the model has been presented by our previous paper 3 l and by Ross and Schofield,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…35 (kT/e) 1/4 as the glass transition density. However, subsequent analysis (111), revealed that the diffusion constant at high densities fits well an equation of the form…”
Section: Metastable Fluids and Amorphous Solidsmentioning
confidence: 91%
See 2 more Smart Citations
“…35 (kT/e) 1/4 as the glass transition density. However, subsequent analysis (111), revealed that the diffusion constant at high densities fits well an equation of the form…”
Section: Metastable Fluids and Amorphous Solidsmentioning
confidence: 91%
“…Several authors have studied the amorphous phase of continuous potential systems, in particular the 3-D Lennard-Jones system (88,96,(104)(105)(106)(107)(108)(109)(110), the soft-core system (66,111), and the Gaussian system (112). It should be noted that in all these systems crystal nucleation has also been observed.…”
Section: Metastable Fluids and Amorphous Solidsmentioning
confidence: 99%
See 1 more Smart Citation